Characterization of aqueous extract of mangosteen (Garcinia mangostana L.) pericarp and its application in the food system - Tan, Poh Lee (2022)
Garcinia mangostana or generally known as mangosteen is one of the abundant plants utilized in numerous applications. Mangosteen pericarp which is supposedly become fruit waste is the predominantly part of plants being reviewed. These agro-food residues are worth to study because it can be one of the attractive sources of polyphenols and to replace the usage of the synthetic food antioxidants. Once the usage of mangosteen pericarp has becoming more popular to be investigated, it may bring positive impact in reducing the environmental pollution. Nevertheless, most of the earlier research on the extraction of mangosteen pericarp were studied by using solvent extraction methods but aqueous extraction of the mangosteen pericarp is still scarce. Thus, in this study, aqueous extraction of mangosteen pericarp was explored with the assisted of enzymes to obtain the bioactive compounds which can be used in food applications. Firstly, water extraction of mangosteen pericarp with the assistance of Celluclast® 1.5l and Pectinex Ultra SPL enzymes was optimized with fractional factorial design by response surface methodology. Optimized conditions obtained were 1.50% w/w of enzymes concentration, 18.75 liquid-solid ratio, reaction temperature at 30°C, pH 3 and reaction time of 30 min and resulted 86.51% of DPPH, 86.77% of ABTS and 21.222 mg GAE/g of total phenolic content. Optimized mangosteen pericarp extract tentatively being identified to contain smeaxanthone m/z 395, apigenin-6-C-glucoside m/z 431, garcimangosone-C m/z 411, α-mangostin m/z 409, gartanin m/z 395, 1,5-dihydroxy-3- methoxy-2-(3-methyl-2-buten-1-yl)-9H-xanthen-9-one m/z 325, 8-desoxygartanin m/z 379 and γ-mangostin m/z 395 based on different retention times, m/z ratios and fragment ions identified by LC-MS/MS. Secondly, mangosteen pericarp extract possessed inhibition activity on four strains of bacteria, Streptococcus pyogenes, Staphylococcus aureus, Streptococcus mutans and Porphyromonas gingivalis with same MIC and MBC values at 15.63 μg/mL, 62.50 μg/mL, 125 μg/mL and 125 μg/mL. MTT assay was performed to evaluate the cytotoxicity level of the mangosteen pericarp extract and the result obtained showed that the optimized extract was nontoxic to the human embryonic kidney cell line, HEK293. Thirdly, two types of functional foods were developed, one was mangosteen pastilles (solid) and another one was mangosteen ready-to-drink beverage (liquid). Three different formulations of functional foods for each category were developed and physicochemical stability and sensory evaluation were performed for storage period of 8 weeks. Moisture content, water activity, color, texture profile analysis and microbiological analysis for the mangosteen pastilles were determined. The moisture content and water activity of the mangosteen pastilles were decreased during storage and the color lightness of the mangosteen pastilles was significantly reduced (p<0.05) during storage stability study. Three formulations of mangosteen pastilles were proven to be shelf life stable. Formulation A with the highest amount of optimized mangosteen pericarp extract, gelatin and carrageenan gum has the highest scores for the aroma, texture, color and overall acceptability. Lastly, pH, total soluble solid, viscosity, color, microbiological analysis and antioxidant capacity (DPPH, ABTS and total phenolic content) of the mangosteen ready-to-drink beverage were performed and observed. A minimal increase in the total soluble solid content and significantly increase (p<0.05) of pH for the three formulations of mangosteen ready-to-drink beverage was observed during 8 weeks of storage stability study. For the first 4 weeks of storage, no microbial count, yeast and mold were detected, however, microbial growth was visible after storage for 4 weeks. Antioxidant capacities and total phenolic content of the mangosteen ready-to-drink beverage decreased during storage study. From the result obtained through the sensory evaluation, there’s no significant difference was seen among the three formulations of mangosteen ready-to-drink beverage; however, the most acceptable formulation of the mangosteen ready-to-drink beverage is formulation A which has the highest amount of optimized mangosteen pericarp extract, mangosteen puree and apple juice concentrate. Enzyme-assisted water extraction of mangosteen pericarp is a green technique that is worth to explore especially for food manufacturer.